Jewish farmers of the Catskills : a century of survival - Lavender, Abraham D. (University Press of Florida, 1995)
"For almost a century, the largest concentration of Jewish farmers outside of Russia or Israel survived as a community in upstate New York, prospering on land that others in the area essentially had abandoned." "Using archival records that date to the nineteenth century and extensive interviews with the farm families and others, Abe Lavender and Clarence Steinberg tell the story of immigrants from Eastern Europe and New York's Lower East Side who came together in the Catskill Mountains with dreams, ambitions, and fortitude to forge a common culture."--Jacket